ACBD5 and VAPB mediate membrane associations between peroxisomes and the ER - Costello, Joseph; Costina, Victor; Findeisen, Peter; Manner, Andreas; Islinger, Markus (The journal of cell biology, 2017)
Peroxisomes (POs) and the endoplasmic reticulum (ER) cooperate in cellular lipid metabolism and form tight structural associations, which were first observed in ultrastructural studies decades ago. PO-ER associations have been suggested to impact on a diverse number of physiological processes, including lipid metabolism, phospholipid exchange, metabolite transport, signaling, and PO biogenesis. Despite their fundamental importance to cell metabolism, the mechanisms by which regions of the ER become tethered to POs are unknown, in particular in mammalian cells. Here, we identify the PO membrane protein acyl-coenzyme A-binding domain protein 5 (ACBD5) as a binding partner for the resident ER protein vesicle-associated membrane protein-associated protein B (VAPB). We show that ACBD5-VAPB interaction regulates PO-ER associations. Moreover, we demonstrate that loss of PO-ER association perturbs PO membrane expansion and increases PO movement. Our findings reveal the first molecular mechanism for establishing PO-ER associations in mammalian cells and report a new function for ACBD5 in PO-ER tethering.